Impact of malnutrition on febrile neutropenia in children with acute lymphoblastic leukemia during induction phase chemotherapy - Marshalla Agnes; Pudjo Hagung Widjajanto; Wahyu Damayanti (Paediatrica Indonesiana, 2018)
Background Acute lymphoblastic leukemia (ALL) is the most common malignancy in children and adolescents. Febrile Neutropenia (FN) is a medical emergency on ALL that often leads to death. Nutrition status assessment on ALL patient is important because malnutrition can reduce the tolerance of chemotherapy, increase incidence of infection and decrease survival rate. Objectives To assess malnutrition as a risk factor for FN in children with ALL. Methods This case-control study was performed at Sardjito Hospital, Yogyakarta on patients aged 1 month to 18 years diagnosed with ALL and undergoing induction phase chemotherapy between January 2013 and December 2015. The case and control subjects were children with and without FN, respectively. Febrile neutropenia was confirmed by patients temperature above 38ÂºC at one measurement and a peripheral neutrophil count of less than 1,000/mm3. Malnutrition was defined as body weight-for-height was between -2 and <-3 standard deviation. Subjects were included using simple random sampling. Result Bivariate analysis showed a significant correlation between malnutrition and FN (OR 2.62; 95%CI 1.07 to 6.45; P=0.03). However, there was no inverse correlation between socioeconomic status and FN (OR 1.1; 95%CI 0.42 to 2.41; P=0.83). There was no correlation between nutritional status and duration of FN (P= 0.48). Conclusion Malnutrition is a risk factor for FN in children with acute lymphoblastic leukemia.